Genetic resistance to gastro-intestinal nematode parasites in red Maasai, Dorper and Red Maasai X Dorper ewes in the sub-humid tropics - Baker, R.L.; Mwamachi, D.M.; Audho, James O.; Aduda, Eric O.; Thorpe, W.R. (Cambridge University Press, 1999)
Resistance to naturally acquired gastro-intestinal (GI) nematode parasite infections (predominantly Haemonchus contortus) was studied in 166 Red Maasai; 230 Dorper and 294 crossbred (Red Maasai X Dorper) ewes in the sub-humid coastal region of Kenya. Live weights (LWT), blood packed-cell volume (PCV) and faecal egg counts (FEC) were recorded at mating, 3 months post mating, 1 week before lambing and 1, 2 and 3 months post lambing for four separate lambings that took place between 1993 and 1996. The Red Maasai ewes were more resistant to GI nematode infections than Dorper ewes as shown by their significantly lower FEC and significantly higher PCV at most of the sampling times over the reproductive cycle. The breed difference for FEC was significant in the lactating ewes but not in the non-lactating ewes. At most sampling times, the crossbred ewes were as susceptible as the Dorper ewes in terms of both PCV and FEC, particularly at the 1 and 2 month post-lambing samplings. Resistance was also mainfested by a lower proportion of ewes having to be treated with an anthelmintic and a lower mortality rate in the Red Maasai than the Dorper. The Red Maasai ewes were significantly lighter by about 1 to 2 kg than the Dorper ewes at all sampling times. There was a significant increase in FEC and decrease in PCV over the first 2 months of lactation in lactating ewes compared with non-lactating ewes. This peri-parturient increase in FEC occurred in both breeds and the crossbred but was more marked in the susceptible Dorper ewes.